Linear IgA bullous dermatosis with Koebner phenomenon in a liver transplant patient - Ptak, Bartosz; Knosala, Emilia; Wąsik, Grażyna; Białynicki-Birula, Rafał; Baran, Wojciech; Batycka-Baran, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Linear IgA bullous dermatosis (LABD) is a rare, acquired autoimmune disease which is characterized by itchy, clustered, subepidermal bullae with linear IgA deposits at the dermo-epidermal junction in direct immunofluorescence assay (DIF). In 1979, Chorzelski and Jab³oñska distinguished LABD as a separate entity from bullous pemphigoid. Occurrence of LABD in Europe is around 0.2–0.5 cases for 1 million people per year [1, 2].